Sectoral Potential Analysis In Economic Development Planning - Rismayanti Rismayanti (Universitas Gorontalo, 2021)
This study purpose to determine the basic sectors and potential economic sector for the economy of Kendari City during 2014-2020, as well as to determine the suitability between the development focus of Kendari City with the leading sector and its potential sector. The analytical tools used are Location Quotient Analysis to know the basic sectors, Shift Share Analysis, and Klassen Typology to know potential and competitive economic sectors in Kendari City. Meanwhile, to determine the suitability of the development focus, descriptive analysis was used.Location Quotient analysis results show that out of 17 sectors, only 3 sectors are non-basic sectors (does not have a comparative advantage) namely agriculture, mining, and government administration. While the other 14 sectors are classified as economic base sectors in Kendari City. The sector with the largest LQ Index is the corporate services sector and the smallest is the mining sector.The results of shift-share analysis and Klassen typology show that there are potential economic sectors and have competitive advantages (competitive), namely the agriculture, mining, electricity procurement, government administration, and health services sectors. The developed but depressed sectors in Kendari City are the processing industry, construction, trade, corporate services, and other services. Meanwhile, 3 sectors are classified as relatively underdeveloped sectors, namely the clean water supply and waste management sector, accommodation, and real estate provision.The results of the descriptive analysis show that of the 3 sectors that focus on the development of Kendari City, there is one sector that is not following the results of the potential sector analysis, namely the infrastructure sector, in this case, the construction and real estate sectors.